Fully coupled thermomechanical simulation of friction stir welding of aluminum 6061-T6 alloy T-joint. (September 2019) - Salloomi, Kareem N.
Abstract: The current study executes a fully coupled thermomechanical simulation of friction stir welding (FSW) process of aluminum 6061-T6 alloy T-joint type using finite element method. The analysis simulation accounts for the three steps of the FSW process which includes: plunging, dwelling, and moving stages. The temperature history, associated stresses and strains generated through the FSW phases, tool reaction force, and time-dependence of the energy dissipation were evaluated. To overcome the shortcomings of purely Lagrangian and Eulerian descriptions, Arbitrary Lagrangian Eulerian (ALE) formulation, adaptive meshing, and the mass scaling were used as techniques to improve sequence modeling of the friction stir welding process. Coulomb's friction law with nonlinear friction coefficient was used to model contact between the tool and T-joint configuration. To verify the numerical results, an experimental setup was constructed to carry out the FSW of a T-joint. Meanwhile, embedded thermocouples were used in the advancing side to measure temperature close to the welding line. The results obtained throughout the simulation study showed that the temperature was symmetrically distributed across the T-joint width, and the temperature contour displayed a high gradient in the weld stirring zone with a V type shape after the plunge stage. Good correlation between numerical and experimental temperature results was obtained with a little shift in the peak value. The results of von-Mises value showed that the maximum stress has been moved from the skin part gradually into the stringer part with the advancement of the tool during plunging. The plastic strain value was higher on the advancing side in comparison with the retreating side. Moreover, the heat generation calculation showed that the frictional dissipation energy was responsible for generating most of the heat needed to obtain a successful FSW.